INFORMATION AND COMMUNICATION TECHNOLOGIES IN HIGHER EDUCATION: THE VIRTUAL LEARNING ENVIRONMENT IN A BLENDED COURSE - Guedes Martinez, Dayra Emile [UNESP]; Bizelli, Jose Luis [UNESP]; Inforsato, Edson do Carmo [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
This article analyzes the training at a higher level in Brazil with the use of information and communication technologies (ICT) in the legal field, pointing out initiatives of the State of Sao Paulo in distance and semi - distance educational projects. We present the results of a completed master's degree research on the use of a virtual learning environment (VLE) in a blended Pedagogy course. The source of the data analyzed in this research consisted of questionnaires applied by the institution responsible for the course, UNESP, to the students and tutors. The items related to VLE were identified and the responses of these groups were analyzed allowing to conclude that both students and tutors had positive perceptions regarding the environment used in the course.
Keywords: ICT in higher education; Blended learning; Virtual learning environment